The role of proactive knowledge sharing in organizational commitment towards employee performance: Evidence in East Java, Indonesia - Hidayah, Tamriatin; Tobing, Diana Sulianti K.; Handriyono, Handriyono; Sukarno, Hari (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of transformational leadership, learning goal orientation, and organizational commitment on the willingness to engage in proactive knowledge sharing and lecturer performance at Private Universities (PTS) in the Besuki Raya area of East Java. The study sampled 373 lecturers using purposive sampling. Adopting a quantitative approach with Structural Equation Modeling (SEM) using AMOS 5.0, the study systematically examines the relationships among the variables. The research reveals that transformational leadership has a significant impact on lecturer performance but not on proactive knowledge sharing. Additionally, the study confirmed that organizational commitment and learning goal orientation positively influence proactive knowledge sharing, but the two do not directly influence lecturer performance. The Sobel test confirms that proactive knowledge sharing fully mediates the relationship between learning goal orientation and lecturer performance. Proactive knowledge sharing is pivotal in translating learning goals into performance gains. While transformational leadership directly boosts outcomes, organizational commitment and learning orientation require knowledge-sharing mechanisms to impact performance effectively. Institutions should foster knowledge-sharing cultures through collaborative platforms, training, and mentorship. Leaders must align transformational practices with knowledge-sharing incentives, while policies addressing lecturer retention and professional development can amplify commitment and learning orientation.